Transitional justice and socio-economic harm : land grabbing in Afghanistan - Saeed, Huma, 1978- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, a Glass House Book, 2023)
"Maintaining the importance of socio-economic issues in devising transitional justice mechanisms, this book examines the widespread practice of land grabbing in Afghanistan. On 3rd September 2003, one hundred armed police officers bulldozed around thirty homes in the Sherpur neighborhood of Kabul, Afghanistan, evicting over 250 people. Historically, the land was part of the property of the Ministry of Defense, of which a zone was allocated to the ministry's employees who had built homes and had lived there for nearly 30 years. After the demolition, however, the land was distributed among 300 high-ranking government officials, including ministers, deputy ministers, governors, and other powerful warlords. Land grabbing in Afghanistan has become a widespread practice across the country. Based on over 50 semi-structured interviews with key informants and group discussions with war victims and local experts, this book examines the relevance of transitional justice mechanism in response to this situation. Following a critical criminological concern with social harm, this book maintains that it is not enough to consider a country's political history of violent conflict and the violation of civil and political rights alone. Rather, to decide on appropriate transitional justice mechanisms, it is crucial to consider a country's socio-economic background, and above all the socio-economic harm inflicted on people during periods of violent conflict. This original and detailed account of the socio-economic challenges faced by transitional justice mechanisms will be of interest to those studying and working in this area in law, politics and development studies"--
Introduction : Setting the scene -- Socio-economic harm in times of violent conflict, transitional justice and critical criminology -- Housing, Land and Property (HLP) loss in violent conflict -- Violent conflict, socio-economic harm, and transitional justice in Afghanistan -- Housing, Land and Property Rights in Afghanistan -- Land grabbing in Afghanistan -- Land grabbing in Afghanistan, economic-state crime and transitional justice -- Transitional justice and criminology : bridging the gap.
OCLC-licensed vendor bibliographic record.
Keywords: Land tenure -- Afghanistan; Right to housing -- Afghanistan; Right of property -- Afghanistan; Violence -- Social aspects -- Afghanistan; Social rights -- Afghanistan; Transitional justice -- Afghanistan; Afghanistan -- Social conditions -- 21st century; LAW / Legal History; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; LAW / Land Use